Why are European countries diverging in their unemployment experience? - Saint-Paul, Gilles (Bonn, 2004)
"During the nineties, unemployment has fallen in a number of European countries while it has remained high in others. The paper discusses potential causes for that evolution in light of recent economic research, emphasizing obstacles to reform due to political constraints, the prevalence of ideology, and agency issues within those bureaucracies concerned with the unemployment problem. Some speculative thoughts are offered as to why those factors might be more stringent in countries where unemployment remained high."